Natural Resources in Latin America and the Caribbean : Beyond Booms and Busts? - Sinnott, Emily (World Bank, 2012)
Throughout, the history of the Latin America and Caribbean (LAC) region, natural resource wealth has been critical for its economies. Production of precious metals, sugar, rubber, grains, coffee, copper, and oil have at various periods of history made countries in Latin America-and their colonial powers-some of the most prosperous in the world. In some ways, these commodities may have changed the course of history in the world at large. Latin America produced around 80 percent of the world's silver in the 16th through 19th centuries, fueling the monetary systems of not only Europe, but China and India as well. The dramatic movements in commodity markets since the early 2000s, as well as the recent economic crisis, provide new data to analyze and also underscore the importance of a better understanding of issues related to boom-bust commodity cycles. The current pattern of global recovery has favored LAC so far. Countercyclical policies have supported domestic demand in the larger LAC economies, and external demand from fast-growing emerging markets has boosted exports and terms of trade for LAC's net commodity exporters. Prospects for LAC in the short term look good. Beyond the cyclical rebound, however, the region's major longer-run challenge going forward will be to craft a bold productivity agenda. With LAC coming out of this crisis relatively well positioned, this may well be possible, especially considering that the region's improved macro-financial resiliency gives greater assurance that future gains from growth will not be wiped out by financial crises. In addition, LAC has been making significant strides in the equity agenda and this could help mobilize consensus in favor of a long overdue growth-oriented reform agenda. But it remains to be seen whether the region will be able to seize the opportunity to boost long-run growth, especially considering the large gaps that LAC would need to close in such key areas as saving, human capital accumulation, physical infrastructure, and the ability to adopt and adapt new technologies.